2006
DOI: 10.1021/cm051274u
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte Stabilized Nanowires from Fe3O4 Nanoparticles via Magnetic Field Induced Self-Assembly

Abstract: Stabilized with a polyelectrolyte complex, superparamagnetic wires were prepared from Fe3O4 nanoparticles and used to fabricate structures of a complex architecture on solid substrates by manipulating the wires in an external magnetic field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
100
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(101 citation statements)
references
References 40 publications
1
100
0
Order By: Relevance
“…77 The nanowires retained the superparamagnetism of the spherical nanoparticles and presented magnetic anisotropy. Magnetization values measured with a magnetic field parallel to the nanowires were higher than that when the field was oriented perpendicular to the wires, consistent with previous reports of Sahoo et al 78 and Sheparovych et al 73 In a follow-up study, the same authors reported a theoretical investigation of the aggregation of individual spherical superparamagnetic nanoparticles under the influence of an external magnetic field. 79 The study was conducted for 11 and 17 nm iron oxide nanoparticles capped with oleic acid, using a Monte Carlo method.…”
Section: Magnetic Assemblysupporting
confidence: 88%
“…77 The nanowires retained the superparamagnetism of the spherical nanoparticles and presented magnetic anisotropy. Magnetization values measured with a magnetic field parallel to the nanowires were higher than that when the field was oriented perpendicular to the wires, consistent with previous reports of Sahoo et al 78 and Sheparovych et al 73 In a follow-up study, the same authors reported a theoretical investigation of the aggregation of individual spherical superparamagnetic nanoparticles under the influence of an external magnetic field. 79 The study was conducted for 11 and 17 nm iron oxide nanoparticles capped with oleic acid, using a Monte Carlo method.…”
Section: Magnetic Assemblysupporting
confidence: 88%
“…Chainlike materials are also considered one dimensional. For magnetic particles, the self-assembled chainlike structures formed by nanoand microparticles attract increasing interest because of their potential application in the fabrication of nano-and microdevices [8][9][10][11]. On the other hand, chainlike structures formed by feeble magnetic particles have received much less attention.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, these magnetite nanoparticles can be fabricated into ordered assembles by applying a magnetic field, yielding ordered alignment of nanoparticles along the magnetic field. [16,17] However, these assembled nanoparticles have limited magnetization anisotropy due to the low aspect ratio of the prepared micro-/nanostructure arrays, especially the 1D arrays. To improve the anisotropy, some micro-/ nanoprocessing methods, such as light/electron-beam lithography, [18] focused ion beam lithography [19] and templating techniques, [20] can be employed to assemble nanoparticles into high-aspect-ratio patterns with designable geometric parameters.…”
mentioning
confidence: 99%